Optimization of Tannic Acid Polymerization to Improve the Efficiency of Dye-Sensitized Solar Cells: Effect of Temperature and Monomer Concentration - Agustini, Dwi; Hardeli, Hardeli; Oktavia, Budhi; Permatasari, Putri (Universitas Andalas, 2025)
This study investigates the effects of temperature and monomer concentration on tannic acid polymerization to enhance dye-sensitized solar cell (DSSC) efficiency. Tannic acid was polymerized using Trimethylolpropane Triglycidyl Ether (TMPGDE) as a crosslinker, with monomer concentrations of 2, 2.5, and 3 grams and temperatures ranging from 30°C to 110°C. UV-Vis analysis revealed a bathochromic shift in poly-tannic acid, indicating increased light absorption in the 200-800 nm range. FTIR confirmed the formation of new ether groups, signifying successful polymerization. The highest DSSC efficiency (8.984%) was achieved with 2.5 grams of monomer at 50°C, significantly outperforming unpolymerized tannic acid (1.35%). The optimal poly-tannic acid has an average molecular weight of 32,610.1568 and a polymerization degree of 19.182. This research demonstrates the potential of tannic acid polymerization for improving DSSC performance, paving the way for more efficient and cost-effective organic solar cells.